The Role of Guidance and Counseling Teachers in Building The Confidence of Grade VIII Students of SMPK ST. Theresia - Toji, liana; Lio , Stefanus (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Self-confidence is a very important psychological aspect in adolescent development, especially for junior high school students. This research aims to analyze the role of guidance and counseling teachers in building self-confidence of grade VIII students at SMPK St. Theresia. The research method used is a case study with a qualitative approach, involving observation, interviews with guidance and counseling teachers, and analysis of guidance and counseling service documents. The results showed that guidance and counseling teachers have a very strategic role in building student self-confidence through various services, namely orientation services for self-introduction, information services about developing self-confidence, individual counseling services to overcome self-confidence problems, group guidance services to train social skills, and consultation services with parents. The implemented programs have proven effective in increasing student self-confidence as indicated by positive changes in the courage to speak in front of the class, active participation in school activities, and better social interaction abilities.